모바일 멀티모달 센서 정보의 앙상블 학습을 이용한 장소 인식 - 이충연(Chung-Yeon Lee); 이범진(Beom-Jin Lee); 온경운(Kyoung-Woon On); 하정우(Jung-Woo Ha); 김홍일(Hong-Il Kim); 장병탁(Byoung-Tak Zhang) (정보과학회 컴퓨팅의 실제 논문지, 2015)
Place awareness is an essential for location-based services that are widely provided to smartphone users. However, traditional GPS-based methods are only valid outdoors where the GPS signal is strong and also require symbolic place information of the physical location. In this paper, environmental sounds and images are used to recognize important aspects of each place. The proposed method extracts feature vectors from visual, auditory and location data recorded by a smartphone with built-in camera, microphone and GPS sensors modules. The heterogeneous feature vectors were then learned by an ensemble learning method that learns each group of feature vectors for each classifier respectively and votes to produce the highest weighted result. The proposed method is evaluated for place recognition using a data group of 3000 samples in six places and the experimental results show a remarkably improved recognition accuracy when using all kinds of sensory data comparing to results using data from a single sensor or audio-visual integrated data only. 본 논문에서는 시각, 음향, 위치 정보를 포함하는 멀티모달 센서 입력 정보로부터 사용자가 위치한 장소의 환경 정보를 학습하고 기계학습 추론을 통해 장소를 인식하는 방법을 제안한다. 이 방법은 음영 지역에서의 정확도 감소나 추가 하드웨어 필요 등 기존 위치 정보 인식 방법이 가지는 제약을 극복 가능하고, 지도상의 단순 좌표 인식이 아닌 논리적 위치 정보 인식을 수행 가능하다는 점에서 해당 위치와 관련된 특정 정보를 활용하여 다양한 생활편의를 제공하는 위치 기반 서비스를 수행하는데 보다 효과적인 방법이 될 수 있다. 제안하는 방법에서는 스마트폰에 내장된 카메라, 마이크로폰, GPS 센서 모듈로부터 획득한 시각, 음향, 위치 정보로부터 특징 벡터들을 추출하여 학습한다. 이때 서로 다른 특성을 가진 특징 벡터들을 학습하기 위해 각각의 특징 벡터들을 서로 다른 분류기를 통해 학습한 후, 그 결과를 기반으로 최종적인 하나의 분류 결과를 얻어내는 앙상블 기법을 사용한다. 실험 결과에서는 각각의 데이터를 따로 학습하여 분류한 결과와 비교하여 높은 성능을 보였다. 또한 사용자 상황인지 기반 서비스의 성능 향상을 위한 방법으로서 제안하는 모델의 스마트폰 앱 구현을 통한 활용 가능성에 대해 논의한다.